An Analysis Of Students’ Difficulties On Reading Comprehension In Explanation Text In SMA YPK Pematangsiantar - Indra Jayanti Damanik; Ridwin Purba; Natasha Hud Elpalma (Bilingual : Jurnal Pendidikan Bahasa Inggris, 2024)
The aim of this research is to find out the difficulties faced by the students on reading comprehension in explanation SMA YPK Pematangsiantar academic year 2022/2023. This research qualitative research based on descriptive data by qualitative research based on descriptive data. Based on the data in the previous chapter has showed that students have some difficulties in comprehend the explanation text or even cannot understand what the explanation text is. Difficulty is something that is complicated to understand or to do. It can be seen from students’ mistakes or error in reading or even comprehend a text. In fact, usually so many senior high school students experience difficulties in reading comprehension. These difficulties result in the students’ bad performance in the reading English explanation text. Meanwhile, reading comprehension also become important part in reading an English text. of course the students at school needed to have this skill